1986
DOI: 10.1002/jcp.1041270103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a pool of non‐recycling transferrin receptors in peripheral sheep reticulocytes

Abstract: Sheep reticulocytes from phlebotomized animals have a total transferrin binding potential that may exceed by an order of magnitude the surface binding capacity. Steady state uptake of transferrin at 37 degrees C is generally less than 50% of the total transferrin binding capacity. During long-term incubation of the reticulocytes, all transferrin binding ability is lost, the ability to internalize being lost most rapidly. The loss in ability to bind transferrin during long-term incubation is independent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There is substantial variation in the number of cell-surface Tf receptors reported in the literature, even in the same species, ranging from 50,000 (Harding et al, 1985) to 242,000 (Van der Heul et al, 1984) for rat reticulocytes. The high SD from the mean value, as previously reported by other authors (Adam et al, 1986), can be attributed to the method of counting reticulocytes and also to differences in their average "stage of maturation." We have determined that there are 134,000 2 60,000 surface binding sites per guinea pig reticulocyte.…”
Section: Maturation Of Guinea Pig Reticulocytesmentioning
confidence: 55%
“…There is substantial variation in the number of cell-surface Tf receptors reported in the literature, even in the same species, ranging from 50,000 (Harding et al, 1985) to 242,000 (Van der Heul et al, 1984) for rat reticulocytes. The high SD from the mean value, as previously reported by other authors (Adam et al, 1986), can be attributed to the method of counting reticulocytes and also to differences in their average "stage of maturation." We have determined that there are 134,000 2 60,000 surface binding sites per guinea pig reticulocyte.…”
Section: Maturation Of Guinea Pig Reticulocytesmentioning
confidence: 55%
“…It is interesting, however, that upon induction, the total binding of TF to cell lysates was substantially larger (4-5 times) than TF binding to the intact cell at 37°C a t steady-state (Table 11, suggesting the appearance of a pool of receptors that was not participating in recycling. With maturing sheep reticulocytes too (Adam et al, 19861, the total receptor pool measured in cell lysates was several-fold greater than the amount of receptor measured by steady-state binding at 37°C to intact cells. Based on this difference, we have earlier proposed the presence of a nonrecycling pool of receptors in maturing red cells.…”
Section: Resultsmentioning
confidence: 98%
“…We observed that new protein synthesis is not required for maturation in vitro (unpublished results), and, although maturation can occur in a chemically defined medium, the presence of serum (2%) increases the rate at which TfR-containing vesicles are formed . Moreover, both reduction of the temperature of incubation and lowering of cellular adenosine triphosphate (ATP) levels reduce the loss of cellular TfR and the formation of TfR-bearing vesicles Adam et al, 1986). These observations suggested to us that components, other than proteins, still synthesized by the reticulocyte might play a role in the maturation process.…”
mentioning
confidence: 80%
“…TfR content in the cells was measured in three ways: 1) [lz5I1Tf binding to reticulocyte lysates, 2) immunoprecipitation of the receptor from 1251-surface labeled cells, and 3) scanning of Coomassie blue-stained gels of immunoprecipitates of total receptor. All three methods have previously been used to quantify receptor content in sheep reticulocytes Adam et al, 1986).…”
Section: Hemin and Receptor Loss During Maturationmentioning
confidence: 99%
See 1 more Smart Citation